PERANCANGAN PENAMBAHAN FITUR PELAPORAN WARGA PADA WEBSITE SINGKAPNEWS.COM UNTUK MASYARAKAT KOTA BEKASI - Sitorus, Anwar Tonggo; Ramadhan, Anisa Novia (TEKNOFILE : Jurnal Sistem Informasi, 2025)
The development of information technology encourages the public to obtain information more quickly, accurately, and interactively. However, Singkapnews.com, as one of the local news portals in Bekasi City, has not yet provided a citizen reporting feature that enables residents to directly submit reports of events. This study aims to design and implement a responsive, secure, and user-friendly citizen reporting feature using the Waterfall software development model. The research process includes user requirements analysis through questionnaires, system design using Unified Modeling Language (UML), implementation with web-based programming languages (HTML, CSS, JavaScript, PHP, and MySQL), and testing using Blackbox Testing as well as user satisfaction evaluation through the Likert Scale. The results show that all functions run according to specifications without errors, while user evaluation indicates a high level of satisfaction with an average score of 4.5 out of 5 in terms of usability, speed, and reporting flow clarity. These findings demonstrate that the addition of a citizen reporting feature can enhance public participation in digital reporting and strengthen Singkapnews.com’s role as a participatory, technology-based media platform.